Development of Interactive Power Point Learning Media to Teach Asking and Giving Opinion Material - Dewi Puja Sayekti; Siti Rofi'ah; Istina Atul Makrifah (Fakultas keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Kendari, 2023)
This study aims to describe the process of developing interactive power point learning media for asking questions and giving opinions to class X students of SMK Hidayatul Mubtadi'in Kanigoro and to describe the results of developing interactive powerpoint learning media for learning materials asking questions and giving opinions to class X students Hidayatul Mubtadi'in Kanigoro Vocational School. In this research and development method refers to ADDIE model. The reason researchers use the ADDIE model in this study is because the ADDIE model has the right steps for the development of the media being developed (Branch, R.M 2009). After the powerpoint interactive learning media was finished, the researcher brought the interactive power point learning media to media material specialists for evaluation. Considering the percentage of experts' validation, namely (87.5%) media experts and (75.0%) material sheets validation. Furthermore, in the product category included in the "Valid" category as a complement to the media, the results of student answers were (62.10%). This means that interactive PowerPoint learning media is feasible to use.